Paradoks universalitas HAM Barat di muka cermin Islam perspektif filsafat hukum dan HAM - Robby Habiba Abror (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
this paper aims at examining the paradox of universality of human rights and trying to bring Western concepts of universality in the context of Islam. Human rights birth of natural philosophy which starts from Newtonian physics, then processed in the philosophy of Locke and Rousseau. So the human rights birth is indeed an effort to combat all forms of oppression by men over other men. Human rights is a concept that start with the state of human nature and hence it is universal. The state of nature in Western philosophy that was later named to the nature of Islam. Violation of human rights is a denial of the concept of universality, so that the West and Islam are required to align rational understanding and cultural particularity of the importance of human rights in the name of justice and humanity. This paper uses philosophy of law and human rights perspective as a method based on the thinking of Western philosophers and to compare with Muslim intellectuals such as Al-Jabiri, Hassan Hanafi and Maududi who had been instrumental in laying a rational approach to human rights in the Islamic theoretical framework. This paper produces an important finding that the concepts of human rights raised by Western philosophers actually been explained clearly in the Quran and hadith, so the universality of Western human rights is no longer a problem for, and can do with scientific interconnectivity, (particularity law) Islam.